Janus monolayer PtSSe under external electric field and strain: A first principles study on electronic structure and optical properties - Vo, Dat D.; Vu, Tuan V.; Al-Qaisi, Samah; Tong, Hien D.; Le, T.S.; Nguyen, Chuong V.; Phuc, Huynh V.; Luong, Hai L.; Jappor, Hamad R.; Obeid, Mohammed M.; Hieu, Nguyen N. (Superlattices and microstructures, 2020)
The effect of biaxial strains εb and electric field E on the electronic structure and optical properties of Janus monolayer PtSSe was studied by Density Functional Theory (DFT). A reasonable band gap of PtSSe was found to be 1.547 eV. In the infrared region, both biaxial strains and electric fields result in noticeable enhancement of the electronic structure as well as optical properties of PtSSe. Especially, under biaxial strains, the change of PtSSe band gap obeys the form of an asymmetric concave down parabola. This result confirms the existence of a maximum PtSSe band gap under biaxial strains εb and the possibility of tuning PtSSe band gap to fit the requirement of the optoelectronic devices. The absorption rate in the visible light region of Janus monolayer PtSSe increases sharply and can be altered by strain engineering. Biaxial strain not only alters the absorption intensity but can also significantly shift the position of these absorption peaks. The present study provides additional information about the strain and electric field-induced electronic structure and optical properties of Janus monolayer PtSSe, which should be taken into account for better PtSSe-based devices. •Spin-orbital coupling effect lowers PBE band gap of 1.547 eV–1.388 eV for equilibrium Janus monolayer PtSSe.•Under biaxial strains, band gap of PtSSe has the form of asymmetric concave down parabola with one maximum.•The ability of biaxial strains to tune PtSSe band gap to some values suitable for optoelectronic materials.•Good enhancement of absorption and reflectivity by biaxial strains and electric fields in the infrared and visible regions.